Перспективи дигіталізації державних послуг в країнах-членах ЄС до 2030 року - Наджафлі, Емін Муса огли (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The abstracts of the report are devoted to promising directions of digitization of public services in the EU member states until 2030 and further prospects of taking into account this experience in Ukraine. It is emphasized that the European experience of digitalization of public services becomes not only a source of legal borrowings for deepening legal reforms in the field of digitalization, but also a certain common denominator that Ukraine should achieve in the legal field, implementing legal standards in the field of digitalization of its public administration in the context of the implementation of strategic course of European integration of Ukraine.